A beginner's guide to urban design and development : the ABC of quality, sustainable design - Alvarez, Laura B. (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides invaluable guidance to all those with an interest in placemaking and the built environment, from those with no experience to those who have worked for many years in industry, illustrating key principles that will secure higher quality, more sustainable design in accessible, jargon-free language. The author explains the design process in a straightforward way, exploring the different roles and highlighting the opportunities and limitations different agencies have to influence design over the various stages of the process. Examples from the UK and worldwide look at how the system operates and how best practice can make a real difference on the ground. Case studies examine situations where quality or sustainability fell short - and how this could have been avoided. This book also showcases a variety of evaluation tools, explaining how they operate, and giving guidance on how to create project-specific tools to drive schemes forward. With community empowerment at its core, the book explains technical language and shares bountiful knowledge to broaden place democracy and make influencing design accessible to many, not just a few. This is a book that brings together all the various parties involved in shaping the built environment, demonstrating that collaboration and mutual understanding are key to achieving better quality, more sustainable design"--
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable design; City planning -- Environmental aspects; Sustainable architecture; Sustainable urban development; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development